2018
DOI: 10.4028/www.scientific.net/aef.27.74
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone as Corrosion Inhibitor for Nickel in Acid Solutions

Abstract: In this paper, the possibility of using ceftriaxone (CEFTR) active substance from expired cefort drug as corrosion inhibitor for nickel in acid solutions has been investigated. 0.5 M sulfuric acid and 1 M hydrochloric acid were used as corrosive media in experimental studies. The electrochemical behavior of ceftriaxone and its stability in test solutions have been examined by cyclic voltammetry. Further, the inhibitory effect has been studied by several methods: weight loss measurements, linear polarization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In table 6, the obtained results for ceftriaxone used as additive in copper electrodeposition are presented [63]. Similar, in table 7, the results for ceftriaxone [64], midazolam [65] and caffeine [66] in nickel deposition process are shown.…”
Section: B= -2303rtsupporting
confidence: 61%
See 3 more Smart Citations
“…In table 6, the obtained results for ceftriaxone used as additive in copper electrodeposition are presented [63]. Similar, in table 7, the results for ceftriaxone [64], midazolam [65] and caffeine [66] in nickel deposition process are shown.…”
Section: B= -2303rtsupporting
confidence: 61%
“…It has to be mentioned that the optimum concentration of Ceftriaxone is about 10 -4 M in 0.5 H 2 SO 4 and 10 -5 M in 1 M HCl. Inhibition efficiencies have been determined by weight loss measurements (WLM), Tafel slope method (TSM) and electrochemical impedance spectroscopy (EIS) ( Table 5) [60]. For copper in 3 M HCl, Narasimha Raghavendra et al used expired Famotidine as corrosion inhibitor with an efficiency of 86% after a weight loss test during 4 h, at 0.4 g L -1 drug concentration [61] and expired Naftifine (active substance: naftifine hydrochloride) in 5 M HCl, with 69% efficiency in the same test conditions [62].…”
Section: Expired Drugs As Corrosion Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the inhibitor added (100 mg SN) alone, the results observed that the lost weight has decreased slightly than if this inhibitor was not used, and this indicates the ineffectiveness of the inhibitor SN in decreasing the rate of corrosion of carbon steel in hydraulic acid. As for adding the inhibitor 100 mg CS, we notice that the lost weight and the corrosion speed decrease significantly, and this indicates the effectiveness of this inhibitor (CS) in decreasing the corrosion speed of carbon steel in hydraulic acid (1 M HCl) [30]. When two inhibitors used together (50 mg SN + 50 mg CS), the lost weight and the speed of corrosion decrease significantly, but not as in the case of using CS alone, because the concentration of CS in the mixture has decreased.…”
Section: Influence Of Inhibitors On the Corrosion Behaviour Of Carbon...mentioning
confidence: 87%